Advances in production management systems : initiatives for a sustainable world : IFIP WG 5.7 International Conference, APMS 2016, Iguassu Falls, Brazil, September 3-7, 2016, Revised selected papers /: initiatives for a sustainable world : IFIP WG 5.7 International Conference, APMS 2016, Iguassu Falls, Brazil, September 3-7, 2016, Revised selected papers. (2016) - Unknown
No abstract available